A Study on LPG injection based speed regulator for dual fuel diesel engine - Vo, Tan Chau; Tran, Dang Long; Nguyen, Quoc Sy; Cao, Quang Khai; Nguyen, Thanh Nhan; Le, Minh Hao (Journal of Technical Education Science, 2022)
Diesel engines are popularly interested due to their great economic efficiency and the high amount of harmful emissions released. The conversion of using multi-fuel engines aims to reduce emissions, and diversifying alternative energy sources to replace diesel fuel, is a potential solution. This paper presents a method to convert the fuel system of the DI-diesel engine type Vikyno RV125 to LPG-diesel dual combustion mode and preliminarily evaluate performance characteristics operating with the LPG injection-based speed regulator. An LPG injector controller circuit was actuated to operate the engine with different load modes up to 5.0kW at corresponding engine speeds. The air intake manifold was modified to calibrate the air-mass flow to effective performance. The experimental result revealed that the changed system could operate in LPG-diesel dual combustion mode. The operating stability of the engine was recognized at speeds up to 1600rpm. A study on engine exhaust emissions will be performed in the next research stage.